Effect of the Forming Conditions in the Production of Gamma Alumina Catalyst Support on the Crushing Strength Property - Dhari Jawad, Alaa; Richeh, Ibrahim; Ahmed Saleh, Riad (Iraqi Journal of Chemical and Petroleum Engineering, 2010)
An investigation was conducted for the determination of the effects of the forming conditions in the production of Gamma Alumina catalyst support on the crushing strength property. Eight variables were studied , they are ;binder content which is the sodium silicate , Solvent content which is the water, speed of mixing , time of mixing, drying temperature , drying time , calcinations temperature and the calcinations time Design of the experiments was made by using the response Surface method in Minitab 15 software which supply us 90 experiments . The results of this investigation show that the crushing strength for the dried Gamma alumina extrudate was affected by the drying temperature and the drying time only and there is no interaction effect between the variables studied. Furthermore, the results show that, the crushing strength for the calcined extrudate was affected by the speed of mixing only and the optimum speed is 900rpm. The maximum crushing strength of 38.38 after calcinations and 11.865 Kg/mm after drying were obtained